ANALISIS PENERAPAN SISTEM PENCATATAN AKUNTANSI BERBASIS TIKTOK SHOP PADA TOKO ONLINE ANMA KSHOP - Diah Suci Putri Rahmadhani; Taufik Kurniawan (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
This study aims to analyze the TikTok Shop-based accounting recording system implemented by ANMA KSHOP. A qualitative descriptive method was employed using observation, documentation, and transaction data analysis during the internship period. The results show that ANMA KSHOP utilizes the TikTok Shop dashboard to obtain sales, service fee, and fund receipt information. However, accounting records and inventory management are still handled manually using Microsoft Excel. Although the system supports operational and financial monitoring activities, it remains prone to recording errors, data discrepancies, and inefficiencies in reconciliation processes. SKINTIFIC AHA BHA PHA Exfoliating Pads was identified as one of the main contributors to sales performance during the observation period. An integrated accounting information system connected to TikTok Shop is recommended to improve accuracy, efficiency, and the quality of financial information.